Assessing determinants of perceived ease of use of institutional repositories by lecturers in Nigerian universities (2020)
Institutional repositories (IRs) present platform to disseminate research findings to complement the traditional scholarly communication model. The use of IRs is beneficial to authors, host institutions, libraries and society at large. Despite the numerous benefits of IRs, there is low deposit of scholarly works by lecturers and the investment on IRs seems to be a waste. This study examined determinants of perceived ease of use (PEOU) of IRs by lecturers in Nigerian universities. A survey of lecturers received 857 respondents. Awareness, anchor and adjustment factors were found to be determinants of PEOU of Institutional repositories by lecturers in Nigerian Universities